2012
DOI: 10.1186/1471-2458-12-302
|View full text |Cite
|
Sign up to set email alerts
|

Association between occupational exposure and the clinical characteristics of COPD

Abstract: BackgroundThe contribution of occupational exposures to COPD and their interaction with cigarette smoking on clinical pattern of COPD remain underappreciated. The aim of this study was to explore the contribution of occupational exposures on clinical pattern of COPD.MethodsCross-sectional data from a multicenter tertiary care cohort of 591 smokers or ex-smokers with COPD (median FEV1 49%) were analyzed. Self-reported exposure to vapor, dust, gas or fumes (VDGF) at any time during the entire career was recorded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 38 publications
0
16
0
3
Order By: Relevance
“…Few published studies have evaluated the effect of occupational exposures on other measures of respiratory morbidity in patients with established COPD, and the limited work that does exist is inconsistent. Caillaud and colleagues, in a cross-sectional study of COPD (n = 591), showed that reported exposure to VGDF at any point in the occupational history, compared with no exposure, was associated with increased likelihood of lifetime wheeze (71.9 vs. 61.1%; P = 0.04) but observed no exposure-related differences in dyspnea or HRQOL (13). In a cross-sectional study of male outpatients with COPD (n = 185), Rodriguez and colleagues found that patients reporting exposure to occupational dust, gas, or fumes at any point in their occupational history were more likely to report sputum production (OR, 2.8; 95% CI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Few published studies have evaluated the effect of occupational exposures on other measures of respiratory morbidity in patients with established COPD, and the limited work that does exist is inconsistent. Caillaud and colleagues, in a cross-sectional study of COPD (n = 591), showed that reported exposure to VGDF at any point in the occupational history, compared with no exposure, was associated with increased likelihood of lifetime wheeze (71.9 vs. 61.1%; P = 0.04) but observed no exposure-related differences in dyspnea or HRQOL (13). In a cross-sectional study of male outpatients with COPD (n = 185), Rodriguez and colleagues found that patients reporting exposure to occupational dust, gas, or fumes at any point in their occupational history were more likely to report sputum production (OR, 2.8; 95% CI.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the burden of occupational exposures on COPD outcomes has been limited by small cohort sizes and by the challenges of estimating the effects of multiple risk factors, in particular concomitant smoking. These limitations may explain the heterogeneous findings on the role of occupational exposures in COPD outcomes in the limited number of studies addressing this question (10)(11)(12)(13)(14)(15).…”
mentioning
confidence: 99%
“…Therefore, it seem that long-term exposure to agents present in textile industries leads to obstructive lung disease that has features of both asthma and chronic obstructive pulmonary disease. [16][17][18][19] The duration of employment in the cotton industry was significantly correlated to FEV 1 /FVC, an indicator of obstructive respiratory disease. It has been shown that long-term exposure to cotton dust is associated with obstructive pulmonary disease that progresses with duration of exposure.…”
Section: R T I C L E a R T I C L Ementioning
confidence: 99%
“…The extraordinary array of data provided by contemporary cohorts of COPD opens a window to new research questions, as demonstrated by Paulin and colleagues. Gray areas in need of further exploration, which could be developed using these data, include the role of early small airway involvement, the differences in disease progression according to exposure history, clinical and imaging phenotypes of occupational COPD, sex differences, and genetic interactions as determinants of outcomes and disease (16)(17)(18)(19).…”
Section: Causality Established Time To Focus On Effect and Phenotypesmentioning
confidence: 99%